Gastrointestinal digestion of dietary advanced glycation endproducts increases their pro-inflammatory potential. Issue 15 (5th July 2021) - van der Lugt, T.; Vrolijk, M. F.; Bovee, T. F. H.; van Leeuwen, S. P. J.; Vonsovic, S.; Hamers, A.; Opperhuizen, A.; Bast, A.
Abstract : Digestion of dietary advanced glycation endproducts (dAGEs) increases its pro-inflammatory potential  in vitro . Abstract : Thermal treatment of food products leads to the formation of dietary advanced glycation endproducts (dAGEs). It was previously shown that dAGEs induce TNF-α secretion in human macrophage-like cells. To what extent gastrointestinal digestion of dAGEs influences these pro-inflammatory effects and what the implications of these pro-inflammatory characteristics further down the human gastrointestinal tract are, are currently unknown. In one of our previous studies, dAGEs were digested using the TNO gastroIntestinal Model and analysed for dAGE quantity after digestion. In the current study both digested and undigested dAGEs were used to expose human macrophage-like cells, which were subsequently analysed for TNF-α secretion. In addition, the obtained digests were fractionated, and human macrophage-like cells were exposed to the different fractions to determine whether specific fractions induce TNF-α secretion. The results show that digested dAGEs have an increased pro-inflammatory effect on human macrophage-like cells compared to undigested dAGEs. This paper therefore shows that the digestion of food-components, and specifically dAGEs, plays an important role in determining their biological activity.